RECOGNITIONOFQTL FOR SEED PROTEIN AND OIL CONTENT IN TWO SOYBEAN RECOMBINAT INBRED LINES POPULATIONS - A. Kaleri; L. Li; Y. Zhang; W. Liu; C Jiang; Y. Zhang; C. Liu; A. H. Kaleri; M. M. Nizamani; A. Mehmood; S. Bahadur; W-X. Li1and H. Ning (Journal of Animal and Plant Sciences, 2021)
Enhancing protein and oil amounts in soybean seed is one of the main objectives of breeding programs. The aim of this study was to identify quantitative trait loci (QTLs) responsible for protein and oil contents in two recombinant inbred lines (RILs) of soybean. Genotyping of the RIL3613 (Dongnong L13×Heihe 36) and RIL6013 (Dongnong L13×Henong 60) populations was performed using simple sequence repeat markers (SSRs), respectively. Phenotypic data for protein and oil contents in both populations were collected in three different environments. The results indicated wide variations across the lines and among different environments in protein and oil contents, with statistical significance. Nine and five QTLs responsible for protein and oil contents, respectively, explained 6.4515%-13.0368% and 5.7236%-17.7396% of the overall phenotypic variations. Of the detected QTLs, one was previously unknown. These QTLs would be very valuable for breeding soybean with improved nutritional quality.
Keywords: Soybean; Protein content; Oil content; Association mapping population; QTL